Amino-modified cellulose nanocrystals with adjustable hydrophobicity from combined regioselective oxidation and reductive amination. (20th January 2016) - Sirviö, Juho Antti; Visanko, Miikka; Laitinen, Ossi; Ämmälä, Ari; Liimatainen, Henrikki
Highlights: Amphiphilic cellulose nanocrystals with adjustable hydrophobicity were fabricated. CNCs were obtained by acid-free method utilizing oxidative-reduction treatment. Amines with chain length from one to six carbon atom were used in reductive amination. CNCs were uniform regarding their size and charge densities. Hydrophobicity could be adjusted by changing the alkyl chain length. Abstract: The controlled revision of surface properties to alter the hydrophobic features of nanocellulose is a potential technique to obtain materials for many novel applications and to replace oil-based materials acting as amphiphilic polyelectrolytes, among others. In this study, linear amines with increasing chain length were used to adjust the hydrophobicity of amphiphilic cellulose nanocrystals (CNCs). Methyl-, ethyl-, n -propyl-, n -butyl-, n -pentylamine, and n -hexylamine were introduced into a cellulose backbone using combined periodate oxidation and reductive amination in an aqueous environment. A high-pressure homogenizer was used to liberate a highly transparent (over 85% at visible light range) nanocrystal dispersion containing CNCs with a length of 73–131 nm and a width of 5–6 nm. All of the CNCs had similar charge density but the hydrophobicity, indicated by the contact angle measurement from the films, increased gradually from 64° to 109° as a function of amine chain length. Thus, this study demonstrated the fabrication of uniform, amphiphilic nanosized polyelectrolytes with modifiable hydrophobicity.